PERUBAHAN DAN PERKEMBANGAN PANAKAWAN DALAM PEWAYANGAN - Nurhadi Siswanto (Corak : Jurnal Seni Kriya, 2018)
The Panakawan figure in puppet is the original creativity of Indonesian people. Its existence is recognized as having existed before Islam emerged as the political power in the archipelago (Demak). Since the 12th century the figure of Panakawan has been mentioned in Javanese literature and developed in the walls of the temple's reliefs. Even the presence of Panakawan still exists today, with Semar, Gareng, Petruk and Bagong as the characters. Of course there were many different things between Panakawan pre-Islamic times when compared to the Islamic period. These differences were certainly very interesting to study, so they can show the influence of Islam in the world of Wayang. This paper tries to examine the history, changes and development of Panakawan figures in pre-Islamic times and the Islamic period. Using Alvin Boskoff's theory of change, and the theory of the principle of acculturation to Koentjaraningrat's culture, the author tries to examine various changes, and the development of Panakawan figures in wayang. The results of the study show that changes in the pre-Islamic Panamanian era and the Islamic period were changes due to external factors, namely the domination factor of Islamic teachings in Puppet. The strong influence of Islam has caused many changes to occur in the naming, number, form and function of the Panakawan figures.KeyWord: Punakawan, Puppet, changes and Development  Tokoh Panakawan dalam pewayangan adalah asli kreatifitas manusia Indonesia. Keberadaanya diakui telah ada sebelum Islam muncul sebagai kekuatan politik di bumi Nusantara (Demak). Sejak abad 12 tokoh Panakawan telah disebutkan dalam kesusastraan Jawa dan berkembang pada relief dinding-dingding Candi. Panakawanpun keberadaannya masih eksis sampai saat ini, dengan Semar, Gareng, Petruk dan Bagong sebagai tokohnya. Tentunya banyak hal yang berbeda antara Panakawan masa pra Islam bila dibandingkan dengan masa Islam. Berbagai perbedaan tersebut tentulah sangat menarik untuk dikaji, sehingga bisa menunjukkan pengaruh Islam dalam dunia Wayang. Tulisan ini mencoba mengkaji sejarah, perubahan dan perkembangan tokoh Panakawan pada masa pra Islam dan masa Islam. Menggunakan teori Perubahan Alvin Boskoff, dan teori prinsip akulturasi budaya Koentjaraningrat, penulis mencoba mengkaji berbagai perubahan, dan perkembangan tokoh Panakawan dalam pewayangan. Hasil kajian menunjukkan bahwa perubahan Panakawan masa pra Islam dan masa Islam merupakan perubahan karena faktor eksternal, yaitu faktor dominasi ajaran Islam dalam Pewayangan. Kuatnya pengaruh Islam ini telah menyebabkab banyak terjadi perubahan baik pada penamaan, jumlah, bentuk dan fungsi tokoh Panakawan. Kata Kunci: Punakawan, Wayang, Peruabahan dan Perkembangan